2022
DOI: 10.2147/jmdh.s363653
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cancer Survivors’ Adherence to Healthcare Recommendations Made Through a Distance-Delivered Survivorship Program

Abstract: Purpose Ongoing survivorship care allows childhood cancer survivors the opportunity to address treatment-related health problems and improve their quality of life. However, many survivors do not adhere to their healthcare professionals’ recommendations and the factors supporting their adherence remain unclear. Patients and Methods Long-term childhood cancer survivors completed the “Re-engage” program, which assessed survivors’ heath needs and provided individualised rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Additionally, these reinforce the utility of structured web-based curriculums, like the HEAL initiative, in providing widereaching, dedicated, and cost-effective lifestyle guidance and education to parents of CCS (69). The availability and scope of long-term survivorship care after childhood cancer is highly variable and depends on factors such as geographic location, treating institution, and local/regional resources (62,70). Infrequent clinic visits, limited time, and insufficient resources are several systemic factors that limit healthcare providers' ability to provide ongoing, comprehensive education/counseling and meaningful lifestyle interventions (63).…”
Section: Current Intervention Recommendations and Strategiesmentioning
confidence: 89%
See 3 more Smart Citations
“…Additionally, these reinforce the utility of structured web-based curriculums, like the HEAL initiative, in providing widereaching, dedicated, and cost-effective lifestyle guidance and education to parents of CCS (69). The availability and scope of long-term survivorship care after childhood cancer is highly variable and depends on factors such as geographic location, treating institution, and local/regional resources (62,70). Infrequent clinic visits, limited time, and insufficient resources are several systemic factors that limit healthcare providers' ability to provide ongoing, comprehensive education/counseling and meaningful lifestyle interventions (63).…”
Section: Current Intervention Recommendations and Strategiesmentioning
confidence: 89%
“…Nevertheless, Touyz et al found that both adolescents and their parents preferred face-to-face intervention to a web-based one ( 68 ). The lack of consensus regarding an optimal intervention approach is compounded by studies like that of Alchin et al, who found that AYA survivors exhibit limited recall and poor adherence to healthcare recommendations despite the use of a variety of communication modalities for education delivery ( 70 ). In an effort to overcome some of these unique hurdles contemporary investigations are incorporating novel approaches alongside more conventional strategies, such as creating a CCS-directed cookbook and providing guided lifestyle coaching sessions ( 71 , 76 ).…”
Section: Current Intervention Recommendations and Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“… 38 The relationship between worry about cancer-related health problems and its influence on survivorship care engagement appears to be complex. 39 , 40 Adequately educating survivors about their risk of late effects, and the appropriate level of risk-based surveillance needed (eg, GP-led survivorship care vs specialist-led care), without raising their anxiety remains a significant challenge. 40 However, this is important to overcome as risk-stratified models of care become increasingly important to alleviate the pressures of the growing number of survivors on limited services and resources that are available.…”
Section: Discussionmentioning
confidence: 99%